Structures of prostaglandin F synthase from the protozoa Leishmania major and Trypanosoma cruzi with NADP. Issue 5 (1st May 2015) - Moen, Spencer O.; Fairman, James W.; Barnes, Steve R.; Sullivan, Amy; Nakazawa‐Hewitt, Stephen; Van Voorhis, Wesley C.; Staker, Bart L.; Lorimer, Donald D.; Myler, Peter J.; Edwards, Thomas E.
<x xml:space="preserve">Abstract</x> The crystal structures of prostaglandin F synthase (PGF) from both Leishmania major and Trypanosoma cruzi with and without their cofactor NADP have been determined to resolutions of 2.6 Å for T. cruzi PGF, 1.25 Å for T. cruzi PGF with NADP, 1.6 Å for L. major PGF and 1.8 Å for L. major PGF with NADP. These structures were determined by molecular replacement to a final R factor of less than 18.6% (Rfree of less than 22.9%). PGF in the infectious protozoa L. major and T. cruzi is a potential therapeutic target.